A Study on an Anticyclonic-Cyclonic Eddy Pair Off Fraser Island, Australia - Li, Zhibing; Wang, Xiaohua; Hu, Jianyu; Andutta, Fernando Pinheiro; Liu, Zhiqiang (Frontiers in Marine Science, 2020)
This research examines an eddy pair off Fraser Island to the east of the Australian coast in 2009 using the Bluelink Reanalysis data, where the local eddies are poorly understood. This eddy pair formed in July and dissipated in November. We detail the horizontal and vertical structure of the eddy pair in terms of three-dimensional variations in relative vorticity, hydrographic properties, velocity, and dynamic structures, which present notable scales of the eddy pair. An anticyclonic eddy (AE) formed beside the meandering of the East Australian Current (EAC) at 24°S and had a relatively lean structure in the upper 1,000 m towards the EAC. A cyclonic eddy (CE) was generated a month later and interacted with the AE, which had an inconspicuous asymmetric structure towards the AE. Heterogeneity in the AE and CE composing this eddy pair was observed in the horizontal and vertical planes. The AE had a more strengthened and coherent dynamic structure than the CE. The AE and EAC interacted in the generation stage when the EAC path shifted eastward, and then as the EAC swung back to the coastal area, the AE and EAC separated. The AE interacted with the surrounding eddy fields, propagated westward and finally merged again with the EAC. The energy transfer during this process also indicates the interactions among the eddy pair, surrounding eddy field and the EAC. Baroclinic instability (BCI) was a main contributor to the AE in the generation stage. Barotropic instability (BTI) also contributed energy to the AE when it interacted with the EAC but with a much smaller proportion. Both BCI and BTI contributed to the CE for most of its life cycle but to a much less extend than the AE. The zonal heat and salt transported by the AE and CE were calculated based on a Lagrangian framework method, and these amounts were considerable compared with global zonal average heat and salt transported by mesoscale eddies.